Free Cash Flow, Kinerja Keuangan dan Agency Cost Pada Perusahaan Perdagangan Yang Terdaftar Di Bursa Efek Indonesia - Mamay Komarudin; Naufal Affandi (Sains: Jurnal Manajemen dan Bisnis, 2020)
This study aims to analyze how the influence of free cash flow and agency cost on company performance in the trading sector on the Indonesia Stock Exchange. Another objective is to examine agency cost as a moderating variable of the effect of free cash flow on the performance of trading sector companies on the Indonesia Stock Exchange. The research is an explanatory research conducted on trading companies listed on the Indonesia Stock Exchange. The variables of this study include free cash flow and agency cost as the independent variable while the dependent variable is the company's performance which is proxied by the profitability ratio (ROA). The research population was 53 trade sector companies listed on the Indonesia Stock Exchange in 2013 to 2016. The sample selection was done by purposive sampling so that it was selected to be 25 companies. The data analysis tool uses Moderating Regression Analysis (MRA). Research has shown that free cash flow has a negative impact on agency cost. Free cash flow has no effect on company performance. Agency cost increases the effect of free cash flow on company performance